135k views
5 votes
Evaluate:
(3.7 x 10-2) (1.2 x 103)​

User Belgacea
by
5.8k points

1 Answer

5 votes

Answer:


(3.7 * 10^(-2)) (1.2 * 10^3) = 44.4

Step-by-step explanation:

Given


(3.7 * 10^(-2)) (1.2 * 10^3)

Required

Evaluate


(3.7 * 10^(-2)) (1.2 * 10^3)

Remove bracket


(3.7 * 10^(-2)) (1.2 * 10^3) = 3.7 * 10^(-2)*1.2 * 10^3

Rewrite as:


(3.7 * 10^(-2)) (1.2 * 10^3) = 3.7 *1.2* 10^(-2) * 10^3


(3.7 * 10^(-2)) (1.2 * 10^3) = 4.44* 10^(-2) * 10^3

Apply law of indices


(3.7 * 10^(-2)) (1.2 * 10^3) = 4.44* 10^(-2+3)


(3.7 * 10^(-2)) (1.2 * 10^3) = 4.44* 10^1


(3.7 * 10^(-2)) (1.2 * 10^3) = 4.44* 10


(3.7 * 10^(-2)) (1.2 * 10^3) = 44.4

User Meggy
by
4.7k points